PROCESSES FOR THE DIAGNOSIS, PROGNOSIS AND MONITORING OF THE PROGRESSION OF CHRONIC LYMPHOID LEUKAEMIA (CLL) AND/OR OF SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) USING MEMBRANE STIM 1 (2016)
Some embodiments are directed to a process for the diagnosis of systemic lupus erythematosus (SLE) and/or of chronic lymphoid leukaemia (CLL) of a subject who may be suffering therefrom, comprising the in vitro detection of the expression of the fraction of the STIM1 protein located at the cell plasma membrane in a biological sample from human and mice. Some other embodiments are directed to a process for predicting the progression and/or monitoring the progression of CLL and/or of SLE, comprising the in vitro detection of the expression of the fraction of the STIM1 protein located at the cell plasma membrane.